Boosting Immune Function and Disease Bio-Control Through Environment-Friendly and Sustainable Approaches in Finfish Aquaculture: Herbal Therapy Scenarios. Issue 3 (2nd July 2020) - Hoseinifar, Seyed Hossein; Sun, Yun-Zhang; Zhou, Zhigzhang; Van Doan, Hien; Davies, Simon J.; Harikrishnan, R.
Abstract: Aquaculture offers a promising source of economic and healthy protein for human consumption and improved wellbeing. This has led to the development of the aquaculture industry, led through advanced production technologies and culture systems in many parts of the world. The intensification of fish production systems by farmers to meet consumer's needs, as well as to generate increased profits, creates a source of stress and the added occurrence of disease and subsequent loss. The negative environmental effects of chemical use have caused legislation to imposed regulations and restrictions to decrease their therapeutic or prophylactic use in aquaculture. As a result, dietary approaches have been suggested as an alternative. Medicinal herbs have been investigated for use in finfish diets to improve immune response and disease resistance. This review paper discusses the suggested modes of action of the effects of medicinal herbs on fish physiology and the immune systems. In addition, a comprehensive literature review on the effects on bacterial, viral, and parasitic diseases is also presented. An added objective was to address the gap between existing knowledge and future perspectives for the improvement of fish health and disease resistance through the use of natural products.